2019
DOI: 10.5468/ogs.2019.62.5.352
|View full text |Cite
|
Sign up to set email alerts
|

The effect of bee prepolis on primary dysmenorrhea: a randomized clinical trial

Abstract: ObjectivePrimary dysmenorrhea typically occurs with no associated pelvic pathology and is common in adolescents and young women. This study evaluated the effect of bee propolis on relief of primary dysmenorrhea.MethodsThe study was performed in 2018 in Hamadan, in western Iran, among female students with primary dysmenorrhea. Participants were randomly divided into two groups, using balanced block randomization, and were administered a placebo or bee propolis capsules for 5 days during two menstruation cycles.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
1
7
0
3
Order By: Relevance
“…Table 1 shows the extract of the included studies [ 18 20 22 44 45 46 47 48 49 50 ]. This systematic review is based on 10 clinical trials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 1 shows the extract of the included studies [ 18 20 22 44 45 46 47 48 49 50 ]. This systematic review is based on 10 clinical trials.…”
Section: Resultsmentioning
confidence: 99%
“…The first randomized clinical trial regarding this subject took place in the United States [ 18 ], and four subsequent studies in the U.S. examined the long-term effectiveness of chamomile use or its efficacy in diagnosed subjects [ 20 44 45 46 ]. One study was conducted in Indonesia [ 47 ], and four were performed in Iran [ 22 48 49 50 ]. The studies spanned from 2009 to 2022.…”
Section: Resultsmentioning
confidence: 99%
“…The studies of E. Jenabi et al on 86 young women showed that taking bee propolis for 5 days during two menstrual cycles significantly reduced pain, both after the first and the second month, without side effects [16]. This substance contains isoflavones, which belong to the group of polyphenols and have antiviral, antibacterial and anti-inflammatory properties.…”
Section: Alternative Treatmentmentioning
confidence: 99%
“…14 Pada penelitian uji klinis menggunakan bee propolis menunjukkan bahwa bee propolis yang diminum mulai dua hari sebelum menstruasi hingga hari ketiga menstruasi (total 5 hari) dapat mengurangi dismenore primer. 15 18 Brief Pain Inventory (BPI) digunakan untuk menilai kualitas hidup subjek dalam bentuk gangguan akibat nyeri dismenore terhadap aktivitas umum, mood, kemampuan berjalan, pekerjaan, hubungan dengan orang lain, tidur, dan menikmati hidup menggunakan skala 0-10, sebagai berikut: 0 = tidak mengganggu dan 10 = mengganggu. 19…”
Section: Pendahuluanunclassified
“…Pada penelitian pengaruh pemberian bee propolis terhadap dismenore primer, bee propolis diberikan dalam dua siklus menstruasi. 15 Pada penelitian lainnya tentang pengaruh pemberian ekstrak Prasaplai terhadap kualitas hidup, ekstrak tersebut diberikan dalam enam siklus menstruasi. 33 Oleh karena itu, penelitian ini memiliki keterbatasan yaitu tidak dapat mengetahui efek pemberian madu dalam jangka panjang atau membandingkan efek pemberian madu pada siklus pertama, siklus kedua dan seterusnya.…”
Section: Pengaruh Madu Terhadap Kualitas Hidupunclassified